DISTRIBUSI PENGETAHUAN, SIKAP DAN PRAKTIK PEDULI LINGKUNGAN MAHASISWA PGSD, UNIVERSITAS MATARAM - Muhammad Syazali; I Ketut Widiada; Aisa Nikmah Rahmatih; Hasnawati Hasnawati; Nurul Maylida; Husnun Niswati (MO.RI Publishing, 2025)
Understanding the environmentally conscious character among PGSD students is very important to encourage sustainable development and environmental education at the elementary level. Environmental education plays a key role in raising awareness and encouraging behavioral changes that support environmental conservation. Elementary school teachers play a strategic role in instilling these values in children from an early age, so their preparation in this field is vital. This fact has prompted surveys on various research subjects. Among these surveys, only a few involve prospective teachers as subjects, and none have covered prospective elementary school teachers. Therefore, this study will explore the environmental awareness knowledge, attitudes, and practices of PGSD students, analyze the relationship between these three variables, and provide recommendations for developing an environmental education-based curriculum. This survey will involve first-year to fourth-year students in the PGSD Study Program at the Faculty of Teacher Training and Education, Mataram University. The sample size was determined using stratified random sampling. The instruments used were tests and closed questionnaires/surveys with a five-point scale. The data collected will be analyzed descriptively to obtain a classical picture of knowledge, attitudes, and practices related to environmental awareness. The results of the analysis show that PGSD students have good environmental awareness. This is based on the large proportion of students who answered correctly on the knowledge domain test with a dominant proportion, the positive attitude domain with a dominant proportion, and the practice domain with a good frequency with a predominant proportion.